Identification of mutations that cause cell migration defects in mosaic clones. - Liu, Y.; Montell, D.J. (Development, 1999)
Cell movement is an important feature of animal development, wound healing and tumor metastasis; however, the mechanisms underlying cell motility remain to be elucidated. To further our understanding, it would be useful to identify all of the proteins that are essential for a cell to migrate, yet such information is not currently available for any cell type. We have carried out a screen for mutations affecting border cell migration in Drosophila. Mutations that cause defects in mosaic clones were identified, so that genes that are also required for viability could be detected. From 6000 mutagenized lines, 20 mutations on chromosome 2R were isolated that cause defects in border cell position. One of the mutations was dominant while all of the recessive mutations appeared to be homozygous lethal. This lethality was used to place the mutations into 16 complementation groups. Many of the mutations failed to complement cytologically characterized deficiencies, allowing their rapid mapping. Mutations in three loci altered expression of a marker gene in the border cells, whereas the remaining mutations did not. One mutation, which caused production of supernumerary border cells, was found to disrupt the costal-2 locus, indicating a role for Hedgehog signaling in border cell development. This screen identified many new loci required for border cell migration and our results suggest that this is a useful approach for elucidating the mechanisms involved in cell motility.